2012
DOI: 10.1242/jcs.105841
|View full text |Cite
|
Sign up to set email alerts
|

Association of bromodomain BET proteins with chromatin requires dimerization through the conserved motif B

Abstract: Summary BET (bromodomain and extra terminal domain) family proteins are unique among bromodomain-containing proteins in that they not only associate with acetylated chromatin in interphase, but also remain attached to chromosomes during mitosis. Although the two tandem bromodomains are essential to display this behaviour, they do not suffice. In this work we report that a small conserved domain, motif B, is also required. A deletion mutant of this domain dissociates from mitotic chromosomes. However, inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
74
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(83 citation statements)
references
References 52 publications
9
74
0
Order By: Relevance
“…Besides being expressed in neural progenitors, Brd2 is also detected in differentiating neurons of the mantle layer in the developing spinal cord . It has been reported that Brd2 stimulates cell cycle progression (Sinha et al, 2005), and in fact, we have shown that overexpressing Brd2 impairs neuronal differentiation, as it results in elevated expression levels of cyclin D1 and A2 (Garcia-Gutierrez et al, 2012). Thus, the prominent role Brd2 displays during cell proliferation raises the question about its presence in differentiating neurons.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations
“…Besides being expressed in neural progenitors, Brd2 is also detected in differentiating neurons of the mantle layer in the developing spinal cord . It has been reported that Brd2 stimulates cell cycle progression (Sinha et al, 2005), and in fact, we have shown that overexpressing Brd2 impairs neuronal differentiation, as it results in elevated expression levels of cyclin D1 and A2 (Garcia-Gutierrez et al, 2012). Thus, the prominent role Brd2 displays during cell proliferation raises the question about its presence in differentiating neurons.…”
Section: Introductionmentioning
confidence: 77%
“…Interestingly, some BET members have been additionally associated with cell differentiation. In this regard, the family member bromodomain-containing protein 2 (Brd2), besides interacting with the transcription factor E2F and controlling expression of cyclin A2 and D1 in proliferating cells (Belkina et al, 2014;Denis et al, 2000;Garcia-Gutierrez et al, 2012;LeRoy et al, 2008;Sinha et al, 2005), is expressed in differentiating neurons , which might be linked to the neural tube closure defects observed in Brd2-knockout mouse embryos and to the association of mutations in the BRD2 locus with human juvenile myoclonic epilepsy (Gyuris et al, 2009;Shang et al, 2009;Velíšek et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has recently been reported that the motif B is required for association to chromosomes and for homo-and hetero-dimerization between BET proteins. 21) The main function of motif B may not be nuclear retention. It is also possible that there are other domains that serve as a nuclear localization signal or a nuclear export signal.…”
Section: Resultsmentioning
confidence: 99%